A collaborative care intervention to improve opioid prescribing among providers caring for persons with HIV: Impact on satisfaction, confidence, and trust. (1st February 2022) - Colasanti, Jonathan A.; del Rio, Carlos; Cheng, Debbie M.; Liebschutz, Jane M.; Lira, Marlene C.; Tsui, Judith I.; Walley, Alexander Y.; Forman, Leah S.; Root, Christin; Shanahan, Christopher W.; Bridden, Carly L.; Harris, Catherine; et al.
Abstract: Background: HIV clinicians report low confidence and satisfaction prescribing chronic opioid therapy (COT). We hypothesized that the Targeting Effective Analgesia in Clinics for HIV (TEACH) intervention [a system-level improvement to increase guideline concordant care for COT] would improve satisfaction, confidence, and trust among PWH and their clinicians. Methods: We conducted a two-arm, unblinded cluster randomized controlled trial (RCT) to assess the TEACH intervention. Clinicians were randomized in a 1:1 ratio to receive either the TEACH intervention (an IT-enabled nurse care manager, opioid education, academic detailing, and access to addiction specialists) or usual care. Outcomes were the following: clinician satisfaction (primary); confidence prescribing COT; patient satisfaction with COT; and trust in clinician. Intention-to-treat analyses were conducted using linear and logistic regression models. Results: Clinicians (n = 41) were randomized and their 114 patients assessed. At 12 months, the adjusted mean difference in satisfaction with COT was 1.11 points for intervention vs control clinicians (Scale 1–10; 95% confidence interval [CI]: −0.04 to 2.26, p = 0.06). The adjusted mean confidence with prescribing COT was 1.01 points higher among intervention clinicians (Scale 1–10; 95% CI: 0.05–1.96, p = 0.04). There were no significant differences in patient satisfaction with COT (adjusted odds ratio (AOR) 1.17, 95% CI: 0.50–2.76, p = 0.72) or trust in provider (AOR 1.63, 95% CI: 0.65–4.09, p = 0.30). Conclusions: TEACH did not significantly affect prescriber satisfaction, patient satisfaction with pain management or patient trust; however, it did improve prescriber confidence. TEACH is a promising strategy to improve provider prescribing of COT for PWH without adverse patient satisfaction or trust in provider. Highlights: COT monitoring for PWH (TEACH), had a neutral impact on provider satisfaction TEACH improved provider confidence around COT compared to usual care TEACH did not adversely affect patient satisfaction or trust